Tożsamość Innego z perspektywy studentów pedagogiki - Orłowska, Beata A. Orłowska (Kultura-Społeczeństwo-Edukacja, 2015)
In the article, pedagogy students’ attitutude towards identity “Other” has been discussed. Attention has been paid to the role of stereotype in shaping approach to identity “Other” students pedagogy. The importance of knowledge and education of future teachers about stereotypes, identity, and "Other" in the perception of the “Other”.